Influences of formation potential on oxide film of TC4 in 0.5 M sulfuric acid - Wang, Qingrui; Huang, Feifei; Cui, Yi-Tao; Yoshida, Hiroaki; Wen, Lei; Jin, Ying (Applied Surface Science, 2021)
[Display omitted] •Thicker oxide film doesn’t mean better corrosion resistance.•The transformation of TiO2 structure may be attributed to the increase of applied potential.•A model exhibiting the influences of potential on oxide film of TC4 in sulfuric acid is proposed. The correlation between film formation potential and the thickness, valence state, and corrosion resistance of the oxide film on TC4 (Ti-6Al-4V) in 0.5 M sulfuric acid is investigated. Potentiostatic polarization and electrochemical impedance spectra measurements reveal the passivation process and electrochemical properties of TC4 alloy. Relative quantitative X-ray photoelectron spectroscopy and Auger electron spectrum analyses illustrate that the formation of thicker and higher valence state film is promoted by the increase in applied potential. Those passive films formed at the potentials in passive region show good protections, and the corrosion resistance of the passive film becomes larger with the increase in passivation potentials. The TiO2 form in oxide films generated under the above conditions transforms from anatase to rutile with the increase in applied potentials and this transformation is found through comparing with the X-ray absorption spectroscopy of reference oxides.